Formation Mechanism of Basic Magnesium Chlorides Whiskers - Wang, Guosheng; Liu, Yang; Liang, Hai; Zhou, Xiaowei; Wang, Kai (Asian Journal of Chemistry, 2013)
The amorphous magnesium hydroxide [Mg(OH)2], Mg2+, Cl– ions, H2O and [Mg(OH)y]2–y (y = 0,...6) anion coordination-polyhedras were proposed as the basic crystallization growth units to form the basic magnesium chlorides whiskers with the general composition xMg(OH)2·MgCl2·yH2O according to the experiment of the dissolution of MgO and MgCl2 in water and the coordination reaction of Mg2+ and OH– and the phase formation and transition reported in the literature can be easily predicted.